2001
DOI: 10.1161/01.str.32.3.767
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection in Pigs by Exogenous Norepinephrine but not by Cerebral Ischemia–Induced Release of Endogenous Norepinephrine

Abstract: Background and Purpose-Endogenous norepinephrine release induced by cerebral ischemia may lead to small areas of necrosis in normal hearts. Conversely, norepinephrine may be one of the mediators that limit myocardial infarct size by ischemic preconditioning. Because brief ischemia in kidneys or skeletal muscle limits infarct size produced by coronary artery occlusion, we investigated whether cardiac norepinephrine release during transient cerebral ischemia also elicits remote myocardial preconditioning. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
1
18
1
Order By: Relevance
“…Sebbag et al (21) could not protect the dog heart by intracoronary administration of the ␣ 1 -adrenoreceptor agonist methoxamine. In contrast, our results are in close agreement with those of de Zeeuw et al (8) who reported that transient intracerebral hypertension cannot precondition the pig heart despite a major myocardial norepinephrine release, as demonstrated by microdialysis. Also, Kirsch et al (15) recently showed that BD does not trigger preconditioning in the rabbit.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Sebbag et al (21) could not protect the dog heart by intracoronary administration of the ␣ 1 -adrenoreceptor agonist methoxamine. In contrast, our results are in close agreement with those of de Zeeuw et al (8) who reported that transient intracerebral hypertension cannot precondition the pig heart despite a major myocardial norepinephrine release, as demonstrated by microdialysis. Also, Kirsch et al (15) recently showed that BD does not trigger preconditioning in the rabbit.…”
Section: Discussionsupporting
confidence: 94%
“…This is, however, unlikely because myocardial damage possibly induced by catecholamine rarely exceed small foci of necrosis. Finally, it is possible that, although plasma levels of norepinephrine and epinephrine were dramatically increased in our preparation, their concentration within the myocardium remained beyond a given threshold necessary to trigger preconditioning, as suggested by de Zeeuw et al (8).…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, one could expect that an adequate degree and duration of SH may induce protective effect in multiple organs, which may be more advantageous than ischemic preconditioning where the remote protection has not been consistently demonstrated. For example, a brief ischemia in kidneys or skeletal muscle could reduce myocardial infarct size caused by a subsequent coronary occlusion, a transient cerebral ischemia failed to produce the similar cardioprotection (7).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that ischemic preconditioning protects the cardiac cells from injury induced by subsequent ischemia and reperfusion. Pretreatment with norepinephrine [4], a neurotransmitter of sympathetic endings in the heart, was shown to effectively mimic the protective effect of ischemic preconditioning on the heart subjected to ischemia and reperfusion. The protective effect induced by this pretreatment was associated with the induction of cardiac tolerance or adaptation to the subsequent overstimulation of β-adrenoceptors in cardiomyocytes [5] during the ischemia and reperfusion so as to attenuate the consequent cardiac impairment [6].…”
mentioning
confidence: 99%